Hip-Hop, Art, and Visual Culture: Connections, Influences, and Critical Discussions - Munson, Lisa (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Visual art has been tied to hip-hop culture since its emergence in the 1970s. Commentary on these initial connections often emphasizes the importance of graffiti and fashion during hip-hop's earliest days. Forty years later, hip-hop music has grown into a billion-dollar global industry, and its influence on visual art and society has also expanded. This book-length printed edition of Arts collects essays by scholars who explore this evolving influence through their work in art education, cultural theory, and visual culture studies. The topics covered by these authors include discussions on identity and cultural appropriation, equity and access as represented in select works of art, creativity and copyright in digital media, and the use of fine art tropes within the sociocultural history of hip-hop. As a collected volume, these essays make potentially important contributions to broadening the narrative on art education and hip-hop beyond the topics of graffiti, fashion, and the use of cyphers in educational contexts.